2004
DOI: 10.1253/circj.68.1132
|View full text |Cite
|
Sign up to set email alerts
|

Is the Ratio of Transmitral Peak E-Wave Velocity to Color Flow Propagation Velocity Useful for Evaluating the Severity of Heart Failure in Atrial Fibrillation?

Abstract: nalysis of the transmitral inflow (TMF) pattern is widely used for evaluating left ventricular (LV) diastolic function, 1,2 and provides valuable information for the management of heart failure (HF) in patients with sinus rhythm. In particular, a restrictive TMF pattern has been recognized as an ominous sign of congestive HF with high mortality. On the other hand, utilization of the TMF pattern analysis in patients with atrial fibrillation (AF) has not been established because of the lack of atrial contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… 11 E/Vp and the deceleration time of PV diastolic flow were each assessed in 2 studies ( n = 55 and n = 67, respectively) and both parameters showed a high degree of correlation with PCWP. 10 , 21 , 22 , 24 Diastolic PV flow was better than mitral indices for estimating PCWP in one study of 35 AF patients. 10 …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“… 11 E/Vp and the deceleration time of PV diastolic flow were each assessed in 2 studies ( n = 55 and n = 67, respectively) and both parameters showed a high degree of correlation with PCWP. 10 , 21 , 22 , 24 Diastolic PV flow was better than mitral indices for estimating PCWP in one study of 35 AF patients. 10 …”
Section: Resultsmentioning
confidence: 97%
“… 25 Diastolic indices, including E/e’ and E/Vp, have also been shown to correlate with B-type natriuretic peptide (BNP), a biomarker strongly associated with adverse prognosis. 15 , 24 E/e’ was the only echocardiographic variable of LV function related to exercise capacity in 73 patients with AF (multivariate adjusted coefficient β = –0.12; P = 0.032). 17 The same group also showed in one of the only multicentre studies that septal E/e’ was associated with prior ischaemic stroke in 330 AF patients with LVEF >40% (adjusted odds ratio 1.21, 95% CI 1.08–1.37; P = 0.002), unlike clinical and echocardiographic parameters such and age, BNP, or LVEF.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation